Polymorphism of CYP3A4*1G gene as a predictor of the hepatotoxicity of antituberculosis therapy - Poludenko , H.O.; Antonenko , P.B.; Antonenko , K.O.; Makarenko , O.V. (Medicni Perspektivi, 2022)
The risk of anti-tuberculosis (ATB) drug-induced liver injury could be determined by genotype polymorphism of the xenobiotic-metabolizing enzymes. The aim of presented research was the investigation of an impact of CYP3A4*1G polymorphism on liver function in patients with TB during anti-tuberculosis therapy. There were analyzed case histories of 105 patients with newly diagnosed pulmonary TB at Odessa Regional TB Hospital in 2012-2014. We have considered their medical records at the beginning and at the end of inpatient treatment including activity of biochemical indices such as total bilirubin, alanine aminotransferase (ALT), aspartate aminotransferase (AST), and gamma-glutathione transferase (GGT). The genotype CYP3A4*1G, 20230G>A was detected by PCR. At the beginning of the treatment the level of studied biochemical indices was almost the same regardless of CYP3A4*1G genotype. After the conducted in-patient treatment the biochemical indices in fast metabolizers insignificantly increased, while the level of bilirubin dropped by 10.4% (p<0.05). In slow metabolizers after in-patient treatment the serum total bilirubin level increased by 8.0% (p<0.05), the activity of ALT raised by 67.2% (p<0.05), AST – by 37.4% (p>0.05), also the number of the patients with ALT and AST level beyond normal almost doubled. After completion of in-patient treatment in moderate and slow metabolizers serum GGT activity increased by 2.5 times (p<0.05) and 1.3 times (p>0.05) correspondently, among fast metabolizers – on the contrary, the number of the individuals with increased GGT level dropped (p<0.05). Thus in slow metabolizers according to CYP3A4*1G genotype after completion of in-patient stage of anti-TB treatment the level of cytolysis and toxicity indexes was much higher than in fast metabolizers. That is why detection of CYP3A4*1G genotype of TB patients at the beginning of TB treatment could help to recognize a group of the individuals with increased risk of liver injury during therapy.